INTEGRASI NILAI-NILAI ISLAM DALAM PEMBENTUKAN KARAKTER SISWA DI ERA GLOBALISASI - Irsan, Irsan (Institut PTIQ Jakarta, 2025)
This study aims to examine the integration of Islamic values in shaping students' character in the era of globalization. Globalization has a significant impact on cultural and moral values, making character education increasingly important in preparing students to face global challenges. Islamic values, grounded in the Quran and Hadith, offer relevant moral guidance for navigating the complexities of this era. This research employs a descriptive qualitative method with a literature study approach, analyzing secondary data from various credible journals and books. The findings indicate that integrating Islamic values into character education can be achieved through various approaches, including curriculum design, school activities, and teacher role modeling. Challenges in implementation include students' diverse backgrounds and external influences, yet opportunities arise through information access and global collaboration. The study concludes that a comprehensive and systematic integration of Islamic values is essential to developing students with strong character, noble ethics, and the ability to contribute positively to the global community